Fitria Dianingsih Anugrah Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Ulang Produk Maskara Wardah Di Kota Bandung - Herawati, Siti; Anugrah, Fitria Dianingsih (Universitas Islam Kadiri, 2024)
This research purposelly to established the impact of product quality and price on repurchase interest in Wardah mascara products in the city of Bandung. By paying attention to the level of marketing within the company, it is hoped that it can make a big contribution in increasing repurchase interest. This research using quantitative methods also using a Likert scale as measurement. The population this research was using female consumers who has used Wardah mascara products in the last 1 year, a sample of 90 research respondents. Primary data was estblish by distributing questionnaires via G-form to 90 respondents. The data analysis technique using classic assumption test also multiple regression test with the SPSS version 26 stone tool. The yields of the T test provide that product quality on repurchase interest is obtained by Tcount of -1.090 < Ttable 1.66256 with a significance of 0.279 > 0.05 which means Product quality has negative also partially insignificant impact towards repurchase interest. Price on repurchase interest Tcount 8.750 > Ttable 1.66256 with a significance of 0.000 <0.05 meaning that the price influence on repurchase interest has positive significant impact. Based on the F test, the Fcount value is 40.528 > Ftable 3.10 with a significance of 0.000 <0.05 so it can be interpreted that product quality and price have a simultaneous influence on repurchase interest. Keywords: Product quality, price, repurchase interest.